Pengaruh Brand Image Dan Digital Marketing Terhadap Keputusan Pembelian Pada Produk Pakaian Merek Sylvia di Marketplace Tiktok Shop - Muhammad Naufal Mushaddaq (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2025)
This study is motivated by the significant decline in sales experienced by the Sylvia brand on the TikTok Shop platform during the July-August 2024 period when not using paid advertising, as well as a large sales gap compared to major competitors where Sylvia's flagship product only achieved sales of 2,945 units compared to competitors who reached more than 10,000 units as of December 2024. This study aims to analyze the effect of brand image and digital marketing on purchasing decisions for Sylvia brand Muslim clothing products at TikTok Shop. The research uses quantitative methods with descriptive approaches and verification analysis. Sampling using purposive sampling technique with the Slovin formula, resulting in 100 respondents. Data were collected through questionnaires. Data analysis using multiple linear regression. The results showed that brand image and digital marketing have a significant positive effect on purchasing decisions, with digital marketing having a greater influence (0.652) than brand image (0.291). The findings imply that Sylvia needs to prioritize digital marketing strategies while still building a strong brand image to increase consumer purchasing decisions.